Project Sammaan - Rosenthal, Jean W., 1945-; Elias, Jaan (London : SAGE Publications Ltd, 2017)
With funding from the Bill & Melinda Gates Foundation, Project Sammaan brought together a stellar group of designers, architects, and social science researchers to tackle one of the developing world's leading problems open defecation in crowded urban settings. Initial planning and surveys began in 2011. With an official kickoff meeting in April 2012, the Sammaan team planned to begin work with city officials in two Indian cities, Bhubaneswar and Cuttack, to build 120 community toilets in city slums by February 2013. Furthermore, the project team hoped to develop research from the effort to create a model that could be used by other communities, completing the research in 2014. However by the late fall of 2013, not a single community toilet had its plans approved, much less built. Various partners believed that the initial vision of the project had been compromised, and the Gates Foundation was refusing to give the project any more money. Observers wondered if the project was fatally stalled and what had gone wrong?
Originally published in Rosenthal, J., & Elias, J. (2014). Project sammaan. 14-012. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/project-sammaan/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Project Sammaan; Public toilets -- India -- Bhubaneswar; Public toilets -- India -- Cuttack